INDIA’S EDUCATION SYSTEM AMONG THE BEST - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, October 2015 – Many may not be aware that the educational facilities in India are considered as among the best, as evidenced by the success in the collaboration between Universiti Sains Malaysia (USM) and India via the International Medical Programme (IMP) with KarnatakaLingayat Education Society (KLE), which will see its first batch of students graduating this year.